Interview data on employment in the wage economy, food security, and effects on the traditional economy in Paulatuk NWT, April 2008 to August 2009. - Cindy Dickson, Council Of Yukon First Nations; Zoe Todd, Department Of Resource Economics; Brenda Parlee, Department Of Resource Economics; Paulatuk Community Corporation; Paulatuk Hunters And Trappers Committee (Canadian Cryospheric Information Network, 2016)
The data consists of 22 semi-directed interviews, with quantitative survey questions and open-ended interview questions. Interviews are in the form of audio files and transcriptions. 2 interviews were done in Inuvik, and 20 in Paulatuk. In Paulatuk, the 20 participants are between the ages of 20 to 83, with 9 participants being female and 11 being male. Extensive notes from a workshop conducted in August 2009 were also taken. 2 additional interviews were conducted in Paulatuk in August 2009. Snowball sampling was used to recruit participants. : Purpose: The research project aimed to gather information regarding employment, harvesting, dietary patterns and social networks in the Inuvialuit Settlement Region; and participant's perceptions of their experiences of employment, harvesting, and food security in the Inuvialuit Settlement Region to better understand the relationships between the wage economy and the traditional economy. : Summary: Not Applicable